Iodine-promoted decarboxylative C–S cross-coupling of cinnamic acids with sodium benzene sulfinates. Issue 31 (5th August 2015) - Chen, Jie; Mao, Jincheng; Zheng, Yang; Liu, Defu; Rong, Guangwei; Yan, Hong; Zhang, Cheng; Shi, Daqing
Abstract: We have developed a practical example of metal-free iodine-promoted decarboxyltive couplings between cinnamic acids and sodium benzene sulfinates, which represents an effective synthesis of vinyl sulfones via C–S bond formation reaction. Graphical abstract: